Suspension of microcarriers for cell culture with axial flow impellers - Ibrahim, S.; Nienow, A.W. (2004)
The suspension characteristics, the agitator speed, Njs, and the mean specific energy dissipation rate, (@eTjs, required to just fully suspend ∼20% wet weight Cytodex 3® microcarrier beads have been studied using a range of different diameter Chemineer HE-3 hydrofoils, a pair of Ekato InterMIG impellers and a six-blade mixed-flow impeller in a baffled vessel of 19.2 1 operating volume containing phosphate buffer saline solution. Flat and modified tank bases were used. Njs values were observed to be in the range of 50 to 90 rev min-1. The use of Zwietering's correlation using existing literature geometric suspension parameters, S, to predict Njs would give values up to 50% higher. The low Njs values obtained in the experiments are attributed to the very small particle-liquid density difference (40 kg m-3), which eased the lifting of the particles from the tank bottom, compared to those studied previously. Also, it was found that at Njs, it took up to about 40 min to suspend all particles as the upper surface of the initially settled bed was scoured away. Previous work has not reported such a long-term phenomenon. With the liquid/particle properties used in this study, the three-blade hydrofoil HE-3 impeller of D/T = 0.39 in a cone-and-fillet based tank was marginally the most efficient; that is, it had the lowest (@eT)js of ∼0.5 × 10-3 W kg-1. However, (@eT)js was less than 1 × 10-3 W kg-1 in most cases with the different size HE-3 hydrofoils, which implies that these geometries would probably be suitable for application in shear-sensitive animal cell culture systems using such microcarriers. © 2004 Institution of Chemical Engineers.